Out of Eden Adam and Eve and the problem of evil. - Kahn, Paul W. 1952- (Princeton Princeton university press, 2007)
"In Out of Eden, Paul Kahn offers a philosophical meditation on the problem of evil. He uses the Genesis story of the Fall as the starting point for a profound articulation of the human condition. Kahn shows us that evil expresses the rage of a subject who knows both that he is an image of an infinite God and that he must die. Kahn's interpretation of Genesis leads him to inquiries into a variety of modern forms of evil, including slavery, torture, and genocide."--BOOK JACKET.
Introduction: the study of evil -- A preliminary meditation on Oedipus and Adam -- Evil and the image of the sacred -- Love and evil -- Political evil: slavery and the shame of nature -- Political evil: killing, sacrifice, and the image of god -- Conclusion: tragedy, comedy, and the banality of evil.
Keywords: Good and evil; 216 -- Goed en kwaad